Flood victims’ evacuation decisions: a semi -nonparametric estimation - Soon, Jan Jan; Kamaruddin, Roslina; Anuar, Abdul Rahim (Emerald Publishing Limited, 2018)
Purpose: The purpose of this paper is to analyse the determinants of actual evacuation decisions of victims of the unprecedented 2014 year-end flood disaster which wreaked havoc across two east-coast states in Malaysia.Design/methodology/approach: The target population of this study is the group of victims affected by the December 2014 flood in the Malaysian east-coast states of Kelantan and Pahang. Sampling frames of the flood victims were obtained from the National Security Council offices of the two states. The empirical analysis of this paper is based on a unique data set obtained from a questionnaire survey of the flood victims. The final working sample consists of 372 respondents.Findings: Important findings from this study are: victims who were given evacuation notices were five times more likely to evacuate, victims who participated in flood awareness programmes were less likely to move to evacuation centres, the further away victims’ homes were from the evacuation centres the more likely they were to evacuate, older victims were less likely to evacuate, larger households were more likely to evacuate, and victims with tertiary education were also less likely to evacuate.Originality/value: This paper is unique because previous studies of Malaysian flood-related disasters are confined to floods of regular magnitude. This paper is also unique because it uses a semi-parametric estimation approach to obtain the marginal effects of the explanatory variables on evacuation decisions.